Keefektifan Model Pembelajaran Think Pair Share (TPS) dan Model Pembelajaran Inkuiri terhadap Hasil Belajar IPA Siswa Kelas V Sekolah Dasar - NURYASANA, ENDANG (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
Science is a subject that provides opportunities for children to think critically, science learning becomes meaningful. In addition to the TPS model the researcher also applied the Inquiry model as an experimental class II, and the reason for selecting the model was as a form of student involvement in the learning process, directing the activities logically and systematically to the learning objectives and developing students' confidence in what was found in the process of inquiry. This research is an experimental study using a quantitative approach with a quasi-experimental method with a non equivalent control group design. The population in this study included all fifth grade students of Al Kautsar Elementary School, SD As Saadah and SD Raden Patah 2017-2018 Academic Year. The sample used in this study was students selected by the Proposal Sampling technique. Data collection was carried out with technical tests in the form of pre-test and post-test, and non-test techniques, namely observations in the form of scientific attitude assessment and skill processes and rating scales to obtain the suitability data of Think Pair Share (TPS) and Inquiry by teachers and students, and documentation. The results of the study were analyzed using prerequisite testing and hypothesis testing. Based on the results of data analysis it can be seen that the TPS (Think Pair Share) model is more effective than Inquiry, used for material about distinguishing changes in objects. Improvement of student learning outcomes can be seen from the results of learning material about distinguishing object changes. In pre-cycle learning, cycle I and cycle II have increased, the average student participation from an average of 61.17 to an average of 81.85. This shows that learning using the TPS (Think Pair Share) learning model applied in this study in learning activities can improve the learning outcomes of fifth grade students of Al Kautsar Elementary School and SD As Saadah Surabaya Surabaya. The increase in student learningoutcomes for natural science subjects in the subject matter changes subject matter has increased.